Cleavage of the Robust Silicon-Fluorine σ-Bond Allows Silicon-Carbon Bond Formation: Synthetic Strategies Toward Ortho-Silyl Aryl Phosphonates - Ji, Suhyun; Kim, Soomin; Lee, Jae Kyun; Lee, Duck-Hyung; Han, Seojung (John Wiley & Sons Ltd., 2025)
A straightforward, mild, and transition-metal-free three-component coupling reaction involving arynes, phosphites, and silyl fluorides was developed through Si？F bond activation. Although the Si？F bond is one of the strongest bonds, Si？C bond formation via Si？F bond cleavage with the assistance of bidentate silicon and phosphonium Lewis acids has been successfully achieved. This unprecedented strategy provides a facile approach for synthesizing ortho-silyl-substituted aryl phosphonates. Notably, this method allows the use of not only dialkylarylsilyl fluorides and diarylalkylsilyl fluorides but also triarylsilyl fluorides as coupling partners, which is uncommon in the field of arylsilane synthesis. Furthermore, a variety of ortho-silyl-substituted aryl phosphonates were produced in moderate to good yields with broad functional group tolerance. Additionally, the versatility of ortho-silyl-substituted aryl phosphonates was demonstrated by the elaboration of the products into a range of silicon-containing compounds.